Location-specific nanoplasmonic sensing of biomolecular binding to lipid membranes with negative curvature. Issue 37 (9th September 2015) - Junesch, Juliane; Emilsson, Gustav; Xiong, Kunli; Kumar, Shailabh; Sannomiya, Takumi; Pace, Hudson; Vörös, Janos; Oh, Sang-Hyun; Bally, Marta; Dahlin, Andreas B.
Abstract : Location-specific nanoplasmonic sensing by monitoring different spectral parameters is used to show how norovirus accumulate in membrane invaginations. Abstract : The biochemical processes of cell membranes are sensitive to the geometry of the lipid bilayer. We show how plasmonic "nanowells" provide label-free real-time analysis of molecules on membranes with detection of preferential binding at negative curvature. It is demonstrated that norovirus accumulate in invaginations due to multivalent interactions with glycosphingolipids.